Hormonal and cytogenetic analyses of reproductive activity of cattle - Degu, Nurhusien Yimer (2011)
The first part of the present study investigated abnormal ovarian cyclicity (AOC) and cystic ovarian diseases (COD) based on plasma progesterone (P4) profiles and ovarian ultrasonogram in 102 cattle which comprised cows open > 90 days postpartum and heifers with delayed age (>24 months) at first calving. Highest incidence of AOC associated with either COD or inactive ovaries occurred in Brangus (BR; 53.3%) and lowest incidence in Kedah Kelantan (KK) cows (12.5%). The difference in AOC was significant (P< 0.05) between KK and the other three breeds. In cows, incidence of COD was highest in FRS (30%), followed by BRF (13.3%), BR (14.3%) and KK (8.7%). Overall, incidence of COD was higher in beef heifers than in cows. Prolonged luteal phase due to luteal cysts was the predominant type of AOC in FRS (66.7%) while cessation of cyclicity due to follicular cysts was the main abnormality in BR (75%) and BRF (76.9%). Thus, this study showed AOC and COD as major causes of reproductive failure in dairy and beef cattle with KK cows being the least affected. Moreover, the combination of P4 data and ultrasonograms was able to differentiate the various types of COD. The study was extended to determine the bulls‟ fertility status. Breeding soundness evaluation (BSE) revealed 3 of the 8 bulls examined had testicle defects and/or poor semen quality. Testicular lesions included testicular degeneration, hydrocele and fibrotic foci. In addition, cytogenetic investigation on 20 animals (13 females and 7 bulls) showed normal cattle chromosome complement of 60 and confirmed the acrocentric Y in KK bulls as of zebu genotype. Thus, the study ruled out chromosomal aberration as a cause of reproductive failure. Measurement of faecal progestin levels to monitor reproductive activity in cattle was another aspect of the present study. Evaluation of modified faecal extraction protocol was 76.8% efficient to recover faecal progestins and hence subsequently used in this study. Matched plasma and faecal samples collected twice a week for 3 months, from cycling as well as pregnant KK and from Brangus cows with either regular cycle or ovarian disturbance, were assayed for plasma P4 and faecal progestin concentrations respectively, by RIA. There was a significant positive correlation (r= 0.6, P< 0.01) between faecal progestin and plasma P4 concentrations in the cycling KK cows, indicating physiological validity of the assay method. Mean faecal progestin concentrations during the follicular phase (FP; 212.6 ± 19.3 ng/g) was significantly (P< 0.01) lower than the luteal phase (LP; 792.4 ± 66.7 ng/g), indicating that the method can differentiate FP from LP. Comparisons between pregnant and cycling KK cows revealed a clear difference whereby mean pregnant faecal progestin concentrations (728.6 ± 33.5ng/g) were significantly (P< 0.01) higher than FP but not LP samples. Plasma P4 level, known to remain >1 ng/ml in pregnant cows, coincided with faecal progestin of >344 ng/g. Hence, faecal progestin concentrations that remain >344 ng/g for >20 days indicate pregnancy in KK cows in the absence of ovarian and/or uterine disorders. In contrast, Brangus cows with ceased ovarian cycle had progestin concentrations of ≤344 ng/g, consistent with plasma P4 of ≤1 ng/ml. Mean concentration of faecal progestin was significantly (P<0.01) lower in cows with cessation of ovarian cycle (86.6 ± 7.0 ng/g) than with regular cycle (392.3 ± 33.8 ng/g). In conclusion, cessation of ovarian cycle is defined as an AOC characterised by weak luteal activity and faecal progestin concentration of ≤344 ng/g for at least 14 days. Therefore, faecal progestin measurements can be potentially used to monitor regular or irregular reproductive cycle. High performance liquid chromatographic (HPLC) separation of faecal extracts followed by RIA analysis revealed 4 immunoreactive metabolites. Subsequent analysis of HPLC fractions by gas chromatography mass spectrometry to identify metabolites was limited by lack of commercial availability of reference standards. However, intact P4 was verified to be undetected in faeces. According to mass spectra library search, metabolites which appeared similar to 5α-reduced pregnanes require future research to confirm and test antibodies against these metabolites for more pronounced profiles.